Analisis Kinerja Unit Lost and Found Dalam Penanganan Bagasi Penumpang Maskapai Lion Air di Bandar Udara Internasional Yogyakarta - Arista Melati Sukma; Febriansyah Ignas Pradana (Jurnal of Management and Social Sciences, 2024)
Air transportation modes have increased after the Covid-19 pandemic, this was offset by an increase in the number of airplane passengers. With the recovery of flight activity, it must be balanced with adequate services, one of which is passenger baggage services. The lost and found unit is a unit that serves arrival passengers' baggage so it must have adequate performance. This study aims to analyze the performance of the lost and found unit of Lion Air at Yogyakarta International Airport. The research method uses a qualitative descriptive method. Data sources for this study were obtained from primary and secondary data. The technique of collecting data by data triangulation uses the method of observing, interviewing, and documenting. Data analysis applies three stages, namely data reduction, presenting, then conclusion. The results of this study are to indicate the performance and constraints of the lost and found units of Lion Air at Yogyakarta International Airport. lost and found unit officers have not carried out their duties properly based on standard operating procedures (SOP) such as inadequate baggage handling, lack of friendly attitude, not punctuality, and lack of ability or expertise of officers. and lost and found units have external and internal constraints such as lack of work equipment, tracking systems, human resources, work environment, and ability, and attitude of officers in handling passenger baggage. It is hoped that the lost and found unit can improve the quality of service for passenger baggage handling.